The development of the first Sudanese grain sorghum hybrids (sorghum bicolor L. Moench) for use under irrigation in central Sudan. - Elasha, Elasha Abdelhay (Gezira Journal of Agricultural Science; Vol 19 No 1 (2021), 2023)
Abstract Afield experiment was carried during 2012 and 2014 seasons at three irrigated locations, Wad Medani, New Halfa and Suki. The hybrids tested were NS -5655, NS-5511 , A8xR2 , A30xR4 , A6xR10 , A41xR8 , and HD-1 used as a check. A8 x R2 , A30 x R4 , A6 x R10 and A41 x R8 were developed by Prof. Elasha A. Elasha, the Sorghum Research Program, the Agricultural Research Corporation, Sudan; while NS -5655, NS-5511 were supplied by Mahgoub sons Company. The land was prepared by disc ploughing, disc harrowing, leveling and ridging . Each entry was sown to five rows of five meters length at 0.8m and 0.3m between ridges and within plants respectively. The design at each site and season was a randomized complete block with four replications. Sowing was on the first week of July and cultural practices pertaining to irrigation, weeding etc. were carried as recommended by the Agricultural Research Corporation. Data was measured on days to 50% flowering, panicle length, plant height; grain yield, stover yield and 100 grain mass. Data was analyzed by IRRISTAT for separate seasons and combined and stability analysis was also carried using the regression procedure of Eberhart and Russel ( 1966). The results showed that, t he mean squares of hybrids, environments and hybrids x environments interaction were highly significant (P<0.01) for grain yield. The overall mean grain yield for irrigated environments for the hybrid A6xR10, NS-5511 and A30xR4 were 4.9, 4.1 and 3.9 t/ha, followed by the hybrid A8xR2 which was 3.8t/ha. These values were 44%, 21%, 15% and 12% more than the grain yield of HD-1 (3.4 t/ha) respectively. The results of grain yield and its stability showed that, the hybrids A6xR10, NS-5511, A30xR4 and A8xR2 were suitable for irrigated conditions.